Uma aplicação do Teorema do Valor Médio - LOPES NETTO, Rubens (2017)
In this work we will present a new theorem that consists of the restriction of the Theorem of the Average Value to a particular case. This theorem applies to real, continuous, and derivable functions in a given interval. Its application allows us to calculate a determinated point on a curve where the straight line tangent to this curve has a specific inclination. As this theorem is related to the concepts of inclination, tangent and secant, this one can be applied in the High School to solve problems of Analytical Geometry that involve such concepts, as we will see in some examples given.